Angular momentum properties of haloes and their baryon content in the Illustris simulation - Zjupa, Jolanta; Springel, Volker (Arxiv, 2016)
The angular momentum properties of virialised dark matter haloes have been measured with good statistics in collisionless N-body simulations, but an equally accurate analysis of the baryonic spin is still missing. We employ the Illustris simulation suite, one of the first simulations of galaxy formation with full hydrodynamics that produces a realistic galaxy population in a sizeable volume, to quantify the baryonic spin properties for more than $\sim$ 320,000 haloes. We first compare the systematic differences between different spin parameter and halo definitions, and the impact of sample selection criteria on the derived properties. We confirm that dark matter only haloes exhibit a close to self-similar spin distribution in mass and redshift of lognormal form. However, the physics of galaxy formation radically changes the baryonic spin distribution. While the dark matter component remains largely unaffected, strong trends with mass and redshift appear for the spin of diffuse gas and the formed stellar component. With time the baryons staying bound to the halo develop a misalignment of their spin vector with respect to dark matter, and increase their specific angular momentum by a factor of $\sim$ 1.3 in the non-radiative case and $\sim$ 1.8 in the full physics setup at z = 0. We show that this enhancement in baryonic spin can be explained by the combined effect of specific angular momentum transfer from dark matter onto gas during mergers and from feedback expelling low specific angular momentum gas from the halo. Our results challenge certain models for spin evolution and underline the significant changes induced by baryonic physics in the structure of haloes.